Eliciting symptoms interpreted as normal by patients with early-stage lung cancer: could GP elicitation of normalised symptoms reduce delay in diagnosis? Cross-sectional interview study. Issue 6 (19th November 2012) - Brindle, Lucy; Pope, Catherine; Corner, Jessica; Leydon, Geraldine; Banerjee, Anindo
Abstract : Objectives: To investigate why symptoms indicative of early-stage lung cancer (LC) were not presented to general practitioners (GPs) and how early symptoms might be better elicited within primary care. Design, setting and participants: A qualitative cross-sectional interview study about symptoms and help-seeking in 20 patients from three south England counties, awaiting resection of LC (suspected or histologically confirmed). Analysis drew on principles of discourse analysis and constant comparison to identify processes involved in interpretation and communication about symptoms, and explain non-presentation. Results: Most participants experienced health changes possibly indicative of LC which had not been presented during GP consultations. Symptoms that were episodic, or potentially caused by ageing or lifestyle, were frequently not presented to GPs. In interviews, open questions about health changes/symptoms in general did not elicit these symptoms; they only emerged in response to closed questions detailing specific changes in health. Questions using disease-related labels, for example, pain or breathlessness, were less likely to elicit symptoms than questions that used non-disease terminology, such as aches, discomfort or 'getting out of breath'. Most participants described themselves as feeling well and were reluctant to associate potentially explained, non-specific or episodic symptoms with LC, even after diagnosis. Conclusions: Patients with early LC are unlikely to present symptoms possibly indicative of LC that they associate with normal processes, when attending primary care before diagnosis. Faced with patients at high LC risk, GPs will need to actively elicit potential LC symptoms not presented by the patient. Closed questions using non-disease terminology might better elicit normalised symptoms.